Pengaruh Riwayat Komorbid Dan Pengetahuan Tentang Penyakit COVID-19 Terhadap Praktik 5M Pada Masyarakat Madiun Tahun 2020 - Puri Ratna Kartini; Arum Suproborini; Yovita Aprilia Putri (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: COVID-19 has become a health problem in the world, including in Indonesia. The high number of COVID-19 transmissions in Indonesia shows the need for massive prevention efforts. In addition to vaccination, the 5M health protocol is an effective way to reduce the number of COVID-19 transmissions. The implementation of the 5M program is influenced by several factors, including knowledge about COVID-19 and history of comorbidities.Methods: This study is an observational-analytic study that aims to analyze the influence of comorbid history during last 3 months and knowledge aobut COVID-19 disease on 5M practice in the Madiun community. 5M practices in this research include wearing masks, washing hands, maintaining distance, avoiding crowds and maintaining immunity. The research design used in this study was cross sectional with the sampling technique used was purposive sampling. Data was obtained by distributing online questionnaires to people living in the Madiun area. The population in this study is the people of Madiun, and the sample in this study is the people of Madiun who voluntarily fill out online questionnaire. The study was carried out for 7 months, starting from June to December 2020.Result: From the results of the Chi square test, it was concluded that the comorbid history and the knowledge about COVID-19 have an effect on 5M practice (comorbid history p = 0.001 and knowledge about COVID-19 p = 0.000).Conclusion : The results of this study are expected to be an input for the government in determining policies to prevent COVID-19, especially in the Madiun area.